Topology of boron substitutional defects in single-walled carbon nanotubes: A first-principles study - Wutthisak Prachamon; Oruethai Jaiboon; Sittipong Komin; Chesta Ruttanapun; Sukit Limpijumnong (My University, 2024)
This is a theoretical study of boron-doped single-walled carbon nanotubes. The same topology of primitive nanodomains, located at different positions on single-walled carbon nanotubes, leads to different electronic band structures. We propose a ϕ term. Density functional theory was corrected for van der Waals interactions and used to carry out the periodic boundary condition geometry optimization, where boron formed the topologies of primitive nanodomains. The calculated bulk structure and local structure spectroscopic parameters can be used for comparison with experimental results to confirm the theoretical models.
Keywords: Carbon Nanotubes in Composites